Coffee Shops as Learning Arenas and Spaces of Student Lifestyle Formation: A Case Study of Hanei Here Coffee in Samarinda City - Aulia, Dwi; Abdullah, Zulkifli (DISCOURSE: Indonesian Journal of Social Studies and Education, 2025)
This study examines the role of Hanei Here Coffee in Samarinda as a learning space and a part of student lifestyle, particularly for students of Mulawarman University. The café has evolved beyond a place for leisure into an informal learning environment that is comfortable, effective, and affordable. The research uses a descriptive qualitative method with a case study approach, based on the theory of Kotler and Keller. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data presentation, and conclusion drawing techniques. The findings show that Hanei Here Coffee supports students’ academic activities and productivity, becoming an integral part of their lifestyle. Its conducive environment meets academic, social, and emotional needs, making it a multifunctional space that plays an important role in students’ daily lives. Thus, the café serves as an alternative learning space and reflects the shifting habits of students in navigating their academic life more flexibly and creatively.